1995
DOI: 10.1039/ft9959103907
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency-induced plasma polymerisation of propenoic acid and propanoic acid

Abstract: Inductively coupled, radiofrequency-induced plasmas of propenoic ('acrylic') acid and propanoic acid, operated at a low electrical power (1-10 W), have been investigated using a combination of mass spectrometry (MS) and deposition-rate measurements. Thin films of plasma polymers of both compounds were deposited onto silicon substrates and analysed by X-ray photoelectron spectroscopy (XPS). The positive-ion MS data obtained from both compounds indicate the presence of species of the form (M + H)+, (2M + H)+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
113
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 12 publications
16
113
0
Order By: Relevance
“…D 1 W to 4.9 š 0.3 nm/min for W r.f. D 20 W. This is consistent with similar findings from organic monomer deposition 25,26 and follows, since higher plasma power increases the number of activated species in the plasma gas phase. 27 Since continuouswave deposition probably proceeds via the rapid step growth polymerisation (RSGP) method, primarily between activated neutral species, an increase in the deposition rate with plasma power is expected.…”
Section: Film Rinsing Stability and Deposition Ratesupporting
confidence: 90%
“…D 1 W to 4.9 š 0.3 nm/min for W r.f. D 20 W. This is consistent with similar findings from organic monomer deposition 25,26 and follows, since higher plasma power increases the number of activated species in the plasma gas phase. 27 Since continuouswave deposition probably proceeds via the rapid step growth polymerisation (RSGP) method, primarily between activated neutral species, an increase in the deposition rate with plasma power is expected.…”
Section: Film Rinsing Stability and Deposition Ratesupporting
confidence: 90%
“…Plasma polymerisation of mixtures of organic vapours have been used to create coatings of varying composition, with the proportion of surface groups relating to multiple monomers included [99,105]. Control over the mixing of the monomers in the gas phase is important for ensuring uniformity of the deposited polymer [106].…”
Section: Defined Surface Chemistry On Planar Substratesmentioning
confidence: 99%
“…A radio frequency field is used to sustain a plasma in an organic vapour, during which the monomer molecules combine to form a cross linked coating on the surface. Since all volatile organic molecules can be polymerised using this method, many different plasma polymer coatings have been fabricated using this technique from allylamine [94][95][96], hexane [97], acrylic acid [98], propanoic acid [98,99], allyl alcohol [100], acetone [101], ethylenediamine [101], diethylamine [101] vinyl acetate [102], methylmethacrylate [102], and toluene [103]. In contrast to conventional polymers, the material chemistry is not a simple linear combination of the monomer units, but rather a cross linked material containing a range of monomer configurations.…”
Section: Defined Surface Chemistry On Planar Substratesmentioning
confidence: 99%
“…Although over the range of variables studied it was not possible to deposit TiO x films, the plasma and film characterizations allow comparison of these results with those observed in the plasma polymerization of hydrocarbon/oxygen mixtures or of monomers that contain the elements carbon, hydrogen and oxygen. Several such studies have been reported in the literature, including the polymerization of allyl alcohol [16][17][18][19], methyl alcohol [20], propargyl alcohol [21,22], propanoic acid [23], ethyl, n-propyl and n-butyl alcohol [24]. Typically, oxygen-containing groups, such as -C-O-, -C_O, and -O-C_O, are observed in films deposited from such monomers.…”
Section: Introductionmentioning
confidence: 98%